Living with the past: ancient Greek philosophy in twenty-first century Nigeria (2017)
Ancient Greek philosophy is important for an integral human development in the twenty-first century as it was in the ancient Greek world. For one, it helps in developing critical thinking ability, a virtue needed to survive in human society; it also helps in building and improving morals since philosophy teaches the psychological factors that help motivate people to be moral. The 20th and 21st centuries, which saw a paradigm shift in the areas of emphasis in Nigeria's higher education began to disregard the foregoing as not being of any serious importance. One of the major victims of this shift was humanistic studies that became regarded as a useless field. This was done in favour of the sciences. Classical Studies and Philosophy, therefore, suffered double jeopardy as they became victims of society's search for meaning and direction within the fold of the Social Sciences and other professional courses. Both disciplines, unfortunately, were misconstrued and erroneously conceived as majorly concerned with abstract realities lacking human contemporary touch. This seriously affected the fortunes of the discipline. This paper focuses on ways in which students in the present context address the questions of relevance and their future. Then, it evaluates pertinent questions such as: what role does philosophy play in contemporary Nigerian society? How can the instructors of the course (ancient Greek Philosophy) make it relevant to both the student and society at large? This paper also discusses the challenges encountered by both the teachers and students of the course in the global age.